2007
DOI: 10.1007/s10517-007-0289-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative status and citrate concentration in rat tissues during experimental hyperthyroidism and melatonin treatment

Abstract: Biochemiluminescence increased, while aconitate hydratase activity and citrate accumulation in tissues of the liver and heart and blood decreased in rats with experimental hyperthyroidism. These changes reflect activation of free radical oxidation, damage to enzyme molecules with reactive oxygen species, and impaired utilization of citrate under pathological conditions. Melatonin treatment during hyperthyroidism normalized aconitate hydratase activity and citrate concentration. Biochemiluminescence study showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…При длительном хроническом патологическом состоянии данная фаза сменяется декомпенсацией, сопровождающейся истощением антиоксидантной системы организма и, соответственно, падением активности антиоксидантных ферментов. При ЭТГ происходило возрастание активности АСАТ и АЛАТ в сыворотке крови крыс, что являлось следствием цитолиза гепатоцитов [9,10].…”
Section: обсуждение результатовunclassified
“…При длительном хроническом патологическом состоянии данная фаза сменяется декомпенсацией, сопровождающейся истощением антиоксидантной системы организма и, соответственно, падением активности антиоксидантных ферментов. При ЭТГ происходило возрастание активности АСАТ и АЛАТ в сыворотке крови крыс, что являлось следствием цитолиза гепатоцитов [9,10].…”
Section: обсуждение результатовunclassified
“…Owing to its lipophilic properties, melatonin can easily penetrate into all organs and tissues, where its antioxidant activity can be implemented [ 14 ]. We have previously found that exogenous melatonin inhibits the development of oxidative stress in rats with toxic hepatitis [ 15 ], type 2 diabetes mellitus [ 16 ], and hyperthyroidism [ 17 ]. In this study, we have used melaxen, a synthetic drug containing melatonin, in the treatment of patients with toxic liver damage caused by excessive alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%